(untitled) (Research, Society and Development, 2021)
The low concentration of N in agricultural soils in the Amazon is a limiting factor for economically and ecologically sustainable agriculture. In this context, the biological fixation of N is of fundamental importance, as it is a natural entry of N into ecosystems. The present work aims to evaluate an infectious capacity of rhizobia and the efficiency in fixing nitrogen in a Yellow Latosol. The present work aims to evaluate the infectious capacity of rhizobia isolates and their efficiency in fixing nitrogen in a Yellow Latosol. The experiment was installed entirely at random, corresponding to a factorial scheme of 6 (4 inoculants without nitrogen + without inoculant without N and without inoculant with N) x 2 (liming and without liming) in 4 repetitions. Liming increased the efficiency of the isolates and rhizobia native to the soil in nodulating the cowpea plants and stimulating the growth of biomass. The native rhizobia of the soil showed symbiotic efficiency similar to the isolates used as inoculants. The FCAN07B isolate is equivalent to nitrogen fertilization in relation to providing biomass gain in cowpea plants. The dose of 20 kg ha-1 of nitrogen was harmful to the nodulation of cowpea.